Cotton proteomics: Dissecting the stress response mechanisms in cotton - Bawa, George; Liu, Zhixin; Zhou, Yaping; Fan, Shuli; Ma, Qifeng; Tissue, David T.; Sun, Xuwu (Frontiers in Plant Science, 2022)
The natural environment of plants comprises a complex set of biotic and abiotic stresses, and plant responses to these stresses are complex as well. Plant proteomics approaches have significantly revealed dynamic changes in plant proteome during responses to stress and developmental processes. Thus, we reviewed the recent advance of cotton proteomics research under changing environmental conditions, considering the progress and challenging factors. Finally, we highlight how single-cell proteomics is revolutionizing plant research at the proteomics level. We envision that future cotton proteomics research at the single-cell level will completely provide a better understanding of cotton's response to stresses.